SURGICAL TREATMENT OF CHILDREN WITH BILATERAL CLEFT LIP AND PALATE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Congenital cleft lip and palate (CCLP) is a severe malformation of the dental system, which is characterized by pronounced structural and functional disorders. In this paper, the issue of surgical treatment in children with bilateral cleft lip was studied by analyzing the sources of domestic and foreign literature. It has been established that most often in patients operated on for congenital bilateral clefts of the upper lip, the following deformations of the middle third of the face, expressed in varying degrees, are encountered. It has been established that most often in patients operated on for congenital bilateral cleft lip, the following deformations of the middle third of the face, expressed in varying degrees, are encountered: discontinuity of the orbicular muscle of the mouth, as evidenced by the low mobility of the central fragment of the lip, flattening of the wings and tip of the nose, upper lips, small vestibule of the mouth in the area of the upper incisors, violation of the shape of Cupid's bow, decrease in the height of the red border, varying degrees of shortening of the columella Particularly severe secondary deformities of the maxillofacial region were observed after the use of atypical variants of cheiloplasty, as well as when using vomer osteotomy and resection of the premaxillary bone.